Educational principles derived from the dialogue of the Prophet, may God bless him and grant him peace, with his wives and their applications in the Muslim family - Al-Mutairi, Noura Hammoud (Journal of Educational and Psychological Sciences, 2025)
The study aimed to reveal the educational principles deduced from the dialogue of the Prophet, may God bless him and grant him peace, with his wives and their educational applications in the Muslim family. It used the deductive and documentary approaches. Among the most prominent results of the study were the following: The educational principles deduced from the dialogue of the Prophet, may God bless him and grant him peace, with his wives were: The following: good reception, speech and listening, the importance of material and moral support between spouses, being patient and not rushing, having patience and self-control, being gentle, courteous and compassionate between spouses, avoiding harm and violence when angry and avoiding obscene and obscene speech, good communication between spouses, dialogue etiquette using lovely words. What is interesting is the importance of emotional communication between spouses, taking the initiative to open a dialogue with the life partner and allocating time to sit with him and exchange dialogue, the suspense and attraction in the dialogue, the importance of honesty and frankness between spouses, the etiquette of reproach in the event of disagreement, showing feelings of love to the life partner, love, respect and appreciation are the origin and anger. Hate is a temporary thing, keeping affection at the end of the dialogue, the principle of good treatment between spouses, the principle of the importance of having fun with a life partner, talking to him and communicating with him, the principle of gentleness, the principle of good listening, the principle of forbearance and patience.